FREEDOM OF POLITICAL EXPRESSION IN PAKISTANI NEWS CHANNEL - Riaz, Andeel; Shahwar, Dr. Deeba; Wafaur Rahman, Syed Muhammad; Ul Abidin, Syed Zain (The journal of contemporary issues in business and government, 2022)
Only in an encouraging climate will the media be able to play a positive role in democracy. They require the essential abilities of detailed reporting that a modern democracy requires. There should also be a structure in place to ensure that they are responsible to the public and uphold moral and professional standards. Media independence is ensured when media organizations are monetarily independent of media owners and the state and function in a competitive atmosphere. The media should also be accessible to as broad a cross-section of society as feasible. Efforts to assist the media should focus on strengthening press rights, increasing media liability, developing media capabilities, and democratizing media access. This theory suggests that media, and in particular television channels, develop the ideas of the people. People who spend more time on television, it tends to be their main source of information. Therefore, the population of present study consisted of all the female and male who study in universities. Four universities selected for the collection of data and the survey sample comprises a total of 120 respondents, 30 respondents taken from each university. The findings of paper indicate that most people rely on electronic media for political news. It influences people’s perceptions and they are becoming politically aware by electronic media especially by the news channels.